Rat Hindlimb Unloading: Soleus and Extensor Digitorum Longus Histochemistry, Mitochondrial DNA Content and Mitochondrial DNA Deletions. Issue 1 (February 2002) - Pesce, V.; Cormio, A.; Fracasso, F.; Lezza, A. M. S.; Cantatore, P.; Gadaleta, M. N.
Abstract : Mitochondrial phenotypic alterations, mitochondrial DNA content and mitochondrial DNA deletions in a slow, Soleus, and a fast, Extensor Digitorum Longus, skeletal muscle of 3- and 15-month-old hindlimb suspended rats have been studied. Cytochrome c oxidase-negative fibers appeared after unloading in all examined animals and their percentage increased with increasing unloading time. After 14 days of suspension the mitochondrial DNA content did not change in 3-month-old but decreased significantly in 15-month-old rats. Soleus was much more affected by unloading than Extensor Digitorum Longus. The mitochondrial DNA deletion of 4834 bp as well as other mtDNA deletions, researched with Long Distance-PCR, were absent in both studied muscles before and after unloading.